Modernising Canada's Agricultural Policies - Jarrett, Peter (OECD Economics Department Working Papers, 2008)
The agricultural sector in Canada is relatively large, compared to those in most other G7 countries. In recent years, the federal and provincial governments have undertaken a number of sectoral reforms to meet the competitiveness and environmental challenges that it faces. The federal government has tried to end a marketing monopoly in the barley market and may do so for wheat as well. The next generation of agriculture and agri-food policy is being finalised, and implementation of the first part of a new framework, Growing Forward, has begun. But a steady stream of ad hoc programmes in recent years has had significant budgetary costs and no doubt created moral hazard among farmers. There is scope for further liberalisation in supply-managed sectors, which are heavily protected and subsidised by consumers. Moreover, Canada's bio-energy production, in particular the production of second-generation bio-ethanol (from cellulose), is under pressure in light of less costly bio-energy production overseas. Against this background, governments are striving to ensure the long-term viability of the sector. This Working Paper relates to the 2008 OECD Economic Survey of Canada (www.oecd.org/eco/surveys/canada)